School-Well Being sebagai Prediktor School Engagement pada Siswa SMA Kuntum Cemerlang Bandung - Ellica Reanna Putri; Heliany Kiswantomo (Humanitas (Jurnal Psikologi), 2025)
This study aims to determine how much influence School Well-Being has on School Engagement in students at SMA Kuntum Cemerlang Bandung. Respondents in the study amounted to 108 Kuntum Cemerlang high school students who were still actively enrolled. This research is a quantitative study with the sampling technique is total random sampling (saturated sampling).  The measuring instrument used for School Well-Being is a modified questionnaire of 27 items. Measurement of School Engagement using a questionnaire which is an adapted design of 23 items. Testing was done with multiple linear regression analysis with SPSS 29 for Mac. As for the results obtained, simultaneously there is an influence of School Well-Being on School Engagement in Students at Kuntum Cemerlang High School. Then, only two dimensions of School Well-Being affect School Engagement, namely Having and Loving. The other two dimensions, Being and Health Status do not influence School Engagement in Students at Kuntum Cemerlang High School. Based on this study, the researcher would like to provide suggestions for future researchers to conduct research by paying attention to other factors that influence School Engagement.